Large Caudate Nucleus on MRI in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
MRI measurements of the head of the caudate nucleus correlated with neuropsychological deficits and behavioral problems in 11 adolescents with ADHD in a study at the University of Barcelona, Spain.